STD/AIDS control among indigenous areas: the simbolic market of upper Rio Negro - Garnelo, Luiza; Araújo, Inesita; Silva, Raimunda M.; Benzaken, Adele; Dias, Luiz C.; Encarnação, Adriana; Sampaio, Sully; Oliveira, Flora M.; Rocha, Esron (Brazilian Journal of Sexually Transmitted Diseases, 2001)
This work using a transdisciplinary perspective was developcd jointly through the articulation of various institutions of the indigenous arcas of the Upper Rio Negro, Northwest Brazilian Amazon. lt sought to include preventative activities for STD/ Aids within the primary health care activities that are being developed by lndigenous Health Agents together with population of aldeas in this region. Within the group of strategies developcd emphasis was made on: Training non indigenous health profissionals within their reference area in diagnosis and treatment; Referral to health centres and health education; Anthropological investigation taking into account the indigenous social representations that may intervene in the way that the educative enessages are accepted or rejected; training Indigenous Health Agents for health education in the indigenous villages; participatory production of ethnically adapted educative material; study of how the material produced was accepted; meetings; assemblies; diverse discussions about the theme of health collegians.